Adopción de menores colombianos por parejas extranjeras del mismo sexo: una perspectiva desde el régimen colombiano (2018)
This research article presents the scant progress and deficiency in our legal system regarding the regulation of international adoption and, more specifically, the legal-social change regarding same-sex marriage, since by imposing equality amongst heterosexual and homosexual marriages, a great breach opens up for the law, which is to decide whether same-sex couples can or cannot adopt. This is because it is necessary that the fundamental rights of minors are not undermined, while uphold the best interest principle defended by the Constitution. Similarly, it analyzes adoption in the field of International Law, studying, first, the fundamental right of the best interest of the minor and the standard minimum (rights and guarantees), as well as the legal status of this legal figure in Colombian jurisprudence and in international agreements. Finally, the text will examine the attitude that States, especially Colombia, should take regarding the adoption of minors by same-sex couples.